Cultura turística y la hospitalidad Babahoyense - Velez Santana, Esther Elizabeth (2019)
The aim of this research is to recognize the importance of hospitality and tourism culture for the development of the Babahoyo canton, in such a way as to encourage the joint participation of the public and private sectors, in order to propose new forms of training and advice on the aforementioned subject to the population, thus achieving the sustainable and sustainable development of tourism and the revitalization of the sector. The project shows that, in recent decades, tourism, culture and the hotel industry have been highlighted as one of the activities that contribute to local, national and global economic growth, as they generate various sources of employment for the population. For the development of the research, exploration techniques were used with a qualitative and quantitative approach, applying surveys to the authorities of MINTUR, GAD, and population in general, resulting in a limited knowledge of tourism culture in the population, poor infrastructure in places used as places of accommodation and weak training to hotel service providers, therefore the public and private company responsible for providing training on the above issues and the owners of establishments dedicated to providing accommodation services should consider the importance of adapting and improving their infrastructure, seeking new ways of learning and training in tourism, thus generating greater demand for visitors who motivate the population to create entrepreneurship that contribute to economic growth, improve the quality of life and social development of the canton.